The mi'rāj in Select Shaykhī, Bābī, and Bahā'ī Texts - Quinn, Sholeh Alysia (Religions, 2023)
The mi‘raj, or ascension of the Prophet Muhammad to heaven, has received a great deal of attention on the part of Islamic scholars and writers, who expanded upon a short Qur’anic passage and communicated their understanding of this episode. Nineteenth century religious leaders associated with the the Shaykhī, Bābī, and Bahā’ī movements continued the practice of commenting on the mi‘rāj. Rather than communicating fixed ideas about the meaning of the mi‘raj, their writings reflect the contexts in which they were composed.